Synthesis of La0.9Sr0.1Ga0.8Mg 0.2O3-δ electrolyte via ethylene glycol route and its characterizations for IT-SOFC - Raghvendra R.; Kumar Singh R.; Singh P. (My University, 2025)
Strontium and magnesium doped lanthanum gallate (La0.9Sr 0.1Ga0.8Mg0.2O3-δ), known as LSGM, was first prepared via ethylene glycol method. This route of preparation showed improved electrical conductivity, better surface area and high density. X-ray diffraction patterns of LSGM sintered at different temperatures indicated that pure LSGM phase was formed after sintering at 1400 C. X-ray Rietveld refinement confirmed the formation of pure perovskite orthorhombic phase of the LSGM. The sintered sample showed 99% relative density. Scanning electron microscopic study of LSGM also depicted fairly densed grain morphology. X-ray photoelectron spectroscopy measurement confirmed the stability of the sintered sample in air and the existence of constituent elements in their characteristic valence states. A surface without porosity was observed in BET measurement. Average thermal expansion coefficient was found to be 9.78×10 -6/ C in the measured temperature range (RT-1000 C). The frequency dependent electrical conductivity of the sample was measured in the temperature range 400-800 C. Total electrical conductivity of the LSGM pellet was found to be 0.056 S cm-1 at 800 C. © 2013 Elsevier Ltd and Techna Group S.r.l.All rights reserved.